(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The Indian mutual fund industry is a very large industry consisting of number of investors. In this era of competition different investor’s have different investment objectives. As the human behaviour is unpredictable, this study helps in finding out the necessary facts regarding investors’ opinion and perceptions regarding mutual fund investment. A mutual fund is the ideal investment vehicle for today’s complex and modern financial scenario. Markets for equity shares, bonds and other fixed income instruments, real estate, derivatives and other assets have become mature and information driven. Small investors face a lot of problems in the share market due to lack of professional advice and lack of information. Mutual funds have come as a much needed help to these investors. The study is to convince customers to take the Mutual Fund route for their investments instead of Fixed Deposits, Recurring deposit and Savings scheme. Both primary and secondary data has been used for achieving the objectives of the study.